HEREDITARY UVEAL MELANOMA: A REVIEW OF LITERATURE AND A CASE REPORT - A. V. Semyanikhina; M. G. Filippova; O. N. Arkhipova; L. N. Lyubchenko (Сибирский онкологический журнал)
Uveal melanoma (UM) is the most common primary intra-ocular malignancy. Uveal melanoma is distinct from other subtypes of melanoma by its molecular and genetic characteristics. Somatic mutations in UM tumor involve genes, such as BAP1, EIF1AX, GNA11, GNAQ and SF3B1, that determine the biology and behavior of a tumor and appear to be predictors of disease. In 25 % of cases, the development of UM is associated with hereditary diseases and can be caused by germline mutations in genes that are responsible for a particular syndrome. Several such syndromes (BAP1-associated syndrome, FAMMM-syndrome, Li-Fraumeni syndrome and etc.) have been identified. In this article we analyze the modern concept of the nature of hereditary UM and present the case of hereditary UM.